SOCIAL SUPPORT AND RESILIENCE ON THE STRESS OF COMPLETING FINAL PROJECTS - Mujidin M Mujidin; Husnul Khotimah Rustam; Harlin Bertha Putri (Journal of Educational, Health and Community Psychology, 2023)
Objective: The aim of this study was to predict the role of social support and resilience of the stress of completing final projectsMethods: This was a non-experimental quantitative study. The population in this study were students of Faculty of Psychology of University X. With the cluster random sampling technique, 50 students were taken as a sample. The data were collected through three main scales, namely a stress scale, social support scale and resilience scale. Subject’s responses were coded and analyzed using SPSS V 16. The multiple linear regression model was used for analysis.Results: This study found that there was a highly significant effect of social support and resilience on stress in completing final projects. In general, stress, social support, and resilience was classified as moderate. Resilience and social support contributes to students’ increased endurance, optimism, self-esteem, willingness, motivation, and acceptance in going through final projects.Conclusion: Social support and resilience of students contribute in evoking energy and understanding that stress when working on final projects is not as terrifying as it seems. With unrelenting confidence, optimism and resilience, students should be able to go through difficult situations